A role of unliganded thyroid hormone receptor in postembryonic development in Xenopus laevis - Sato, Yukiyasu (2007)
A fascinating feature of thyroid hormone (T3) receptors (TR) is that they constitutively bind to promoter regions of T3-response genes, providing dual functions. In the presence of T3, TR activates T3-inducible genes, while unliganded TR represses these same genes. Although this dual function model is well demonstrated at the molecular level, few studies have addressed the presence or the role of unliganded TR-induced repression in physiological settings. Here, we analyze the role of unliganded TR in Xenopus laevis development. The total dependence of amphibian metamorphosis upon T3 provides us a valuable opportunity for studying TR function in vivo. First, we designed a dominant negative form of TR-binding corepressor N-CoR (dnN-CoR) consisting of its receptor interacting domain. We confirmed its dominant negative activity by showing that dnN-CoR competes away the binding of endogenous N-CoR to unliganded TR and relieves unliganded TR-induced gene repression in frog oocytes. Next, we overexpressed dnN-CoR in tadpoles through transgenesis and analyzed its effect on gene expression and development. Quantitative RT-PCR revealed significant derepression of T3-response genes in transgenic animals. In addition, transgenic tadpoles developed faster than wild type siblings, with an acceleration of as much as 7 days out of the 30-day experiment. These data thus provide in vivo evidence for the presence and a role of unliganded TR-induced gene repression in physiological settings and strongly support our earlier model that unliganded TR represses T3-response genes in premetamorphic tadpoles to regulate the progress of development.